P52 Epidemiology of Occupational Extrinsic Allergic Alveolitis reported to SWORD 1996–2014. (12th November 2015) - Barber, CM; Carder, M; Agius, R
Abstract : Introduction: Worldwide, the true epidemiology of occupational EAA is poorly understood. Data from national reporting schemes offers one method of examining the changing demographics of this disease, and comparing the most commonly reported causes. Methods: Data was obtained for all cases of occupational EAA reported to the UK Surveillance of Work-related and Occupational Respiratory Disease (SWORD) scheme since 1996. The likely causative agents for each reported case were grouped into categories, and data compared for the earliest and latest available 5-year time periods (1996–2000 and 2010–2014). An estimate of the annual incidence of occupational EAA was calculated from the estimated number of cases in each time period divided by the average UK working population at that time (data from the Office for National Statistics). Results: Data for the early and late 5-year time periods are presented in Table 1 . The estimated incidence of occupational EAA was similar for the two time periods, but there has been a notable change in reported causation. Occupational EAA due to metalworking fluid, coolant or oil mist exposure has become the most commonly reported cause, responsible for almost a third of all cases. Over the same time period, EAA in mushroom workers has fallen from the joint commonest cause to no reported cases at all. Discussion: The estimated annual incidence of occupational EAA in the UK has remained relatively stable at approximately 1–2 cases per million workers. Although this is likely to represent an underestimate, it is similar to the estimated incidence from reporting schemes in Australia, Catalonia, and the Czech Republic, but an order of magnitude lower than that reported in Finland. Over the last 20 years, EAA due to metalworking fluid exposure has emerged as the most commonly reported cause in the UK. This change has not been noted in other published reporting schemes, where EAA due to agricultural exposures remains the most common aetiology.